REAKSI PSIKOLOGIS DENGAN PENILAIAN QUALITY OF LIFE PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA PADA MASA PANDEMI - Yanti Rosdiana; Wahidyanti Rahayu Hastutiningtyas; Sirli Mardianna Trishinta (STIKes Maharani Malang, 2022)
The COVID-19 pandemic started from the city of Wuhan, precisely in China and spread quickly to all countries in the world. Chronic diseases infected with COVID-19 will affect health conditions and have an impact on the low quality of life for chronic kidney failure. If the quality of life is getting lower then this can have an impact on the patient's psychological reaction, this psychological reaction can be depression, anxiety, and stress. The focus of this study was to determine the relationship between the Quality of Life Assessment of Chronic Failed Patients undergoing hemodialysis and I at Waluya Hospital Malang. This study uses an analytical observation design with a cross sectional approach. The sample according to the inclusion and exclusion criteria, was determined by incidental sampling technique as many as 36 chronic disease patients. Data collection uses the WHOQOL-BREF questionnaire for Quality of Life and Psychological Reactions and has been tested for validity and reliability. The analysis was carried out univariately to see the statistics of the research data and bivariate analysis with spreadaman rank correlation using the SPSS version 16 application. The bivariate test showed that anxiety (r = 0.921, P = 0.000), depression (r = 0.949, P = 0.000), and stress (r=0.949, P=0.000) was positively related to quality of life. There is a relationship between anxiety, stress and depression. Anxiety is the dominant factor related to the quality of life of chronic failure patients undergoing hemodialysis. Keywords: Quality Of Life, Chronic Disease, Psychological Reaction.